Generalized SVPWM Algorithm for Two Legged Three Phase Multilevel Inverter - Devisree Sasi; Jisha Kuruvilla P; Anish Gopinath (Institute of Advanced Engineering and Science, 2013)
This paper establishes the inherent fractal structure in the space vector representation of two legged three phase multilevel inverters. The established fractal structure is utilized to propose a generalized algorithm for space vector PWM generation for two legged multilevel inverters. The voltage space vectors of higher level inverters can be generated from the voltage space vectors of equivalent 2-level inverter. The proposed algorithm can be easily extended to n-level inverters without any computational complexity and it doesn’t use any look up table for sector identification. The paper explains the proposed method for 5-level inverter and simulation results are presented for 2-level, 3-level and 5-level configurations in MATLAB/SIMULINK.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.4099